Comparison of Godunov’s and Relaxation Schemes Approximation of Solutions to the Traffic Flow Equations - Mutua, S.K.; Kimathi, M.E.; J.K Kwanza (International Journal of Scientific and Innovative Mathematical Research, 2014)
In this paper we deal with the study of the traffic flow model that is governed by two hyperbolic equations. By analysing the equations we obtain two real and distinct eigen values which enables us to determine the wave structure of the possible solution to the Riemann problem set up. We then obtain the numerical solution to the Riemann problem that we set up using the Godunov scheme and the relaxation scheme. Finally, we compare the results obtained from these two schemes graphically and explain in details.
Keywords: Eigen values; Riemann problem; Rankine-Hugonoit; Integral curves; Relaxation scheme; Godunov scheme; Weak solution